The Law of Double Consonants in Inuktitut - Dresher, B. Elan; Johns , Alana (Linguistica Atlantica, 2023)
In this article we examine a number of properties having to do with Schneider’s Law in Inuktitut, also referred to as the Law of Double Consonants. This phonological rule simplifies a consonant cluster from two to one when there is an immediately preceding consonant cluster. We argue that although the rule is often characterized as target-ing mixed clusters, consonant assimilation in Labrador Inuttut results in the fact that it only targets geminate clusters. The same is true in Northern Quebec dialects (Massenet 1986). This description of the rule shows eastern dialects (Labrador and Northern Quebec) to be similar to Siglit, a western dialect without extensive consonant assimilation, where the rule targets only geminates and not mixed clusters (Lowe 1985). We review a number of possible explanations of Schneider’s Law, and propose an account based on syllable government of codas.